A Truncated Form of HpARI Stabilizes IL-33, Amplifying Responses to the Cytokine - Chauché, Caroline; Vacca, Francesco; Chia, Shin Li; Richards, Josh; Gregory, William F.; Ogunkanbi, Adefunke; Wear, Martin; McSorley, Henry J. (Frontiers in Immunology, 2020)
The murine intestinal nematode Heligmosomoides polygyrus releases the H. polygyrus Alarmin Release Inhibitor (HpARI) - a protein which binds to IL-33 and to DNA, effectively tethering the cytokine in the nucleus of necrotic cells. Previous work showed that a non-natural truncation consisting of the first 2 domains of HpARI (HpARI_CCP1/2) retains binding to both DNA and IL-33, and inhibited IL-33 release in vivo. Here, we show that the affinity of HpARI_CCP1/2 for IL-33 is significantly lower than that of the full-length protein, and that HpARI_CCP1/2 lacks the ability to prevent interaction of IL-33 with its receptor. When HpARI_CCP1/2 was applied in vivo it potently amplified IL-33-dependent immune responses to Alternaria alternata allergen, Nippostrongylus brasiliensis infection and recombinant IL-33 injection, in direct contrast to the IL-33-suppressive effects of full-length HpARI. Mechanistically, we found that HpARI_CCP1/2 is able to bind to and stabilise IL-33, preventing its degradation and maintaining the cytokine in its active form. This study highlights the importance of IL-33 inactivation, the potential for IL-33 stabilisation in vivo, and describes a new tool for IL-33 research.